Impact of MRI timing on tumor volume and anatomic displacement for brain metastases undergoing stereotactic radiosurgery. Issue 6 (28th July 2021) - Kutuk, Tugce; Tolakanahalli, Ranjini; Williams, Andre; Tom, Martin C; Vadhan, Jason D; Appel, Haley; Hall, Matthew D; Wieczorek, D Jay J; Davis, Stephen; McDermott, Michael W; Ahluwalia, Manmeet S; Mehta, Minesh P; et al.
Abstract: Background: The objective of this study was to evaluate the impact of the time interval between planning imaging and stereotactic radiosurgery (SRS) delivery on tumor volumes and spatial anatomic displacements of brain metastases (BM). Methods: Consecutive patients diagnosed with BM treated with SRS over a 3-year period were evaluated. Only patients who underwent an institutionally standardized diagnostic MRI (MRI-1) and a treatment planning MRI (MRI-2) were included. The impact of histology, inter-scan time interval, lesion location, tumor volume, and diameter were evaluated on final lesion diameter, volume, anatomic displacement, and ultimate need for change in management (ie, expanding margins, rescanning). Results: 101 patients (531 lesions) with a median inter-scan time interval of 8 days (range: 1-42 days) met the inclusion criteria. The median percentage increase in BM diameter and volume were 9.5% (IQR: 2.25%-24.0%) and 20% (IQR: 0.7%-66.7%). Overall, 147 lesions (27.7%) in 57 patients (56.4%) required a change in management. There was a statistically significant relationship between initial tumor diameter (cm) and change in management (OR: 2.69, 95% CI: 1.93-3.75; P < .001). Each day between MRI-1 and MRI-2 was associated with a change in management with an OR of 1.05 (95% CI: 1.03-1.07; P < .001). Conclusions: Changes in tumor diameter, volume, and spatial position occur as a function of time. Planning imaging for SRS is recommended to occur in close temporal proximity to treatment; for those with delays, a larger setup margin may need to be used to ensure tumor coverage and account for positional changes.